Int. J. Adv. Res. Biol. Sci. 2018
DOI: 10.22192/ijarbs.2018.05.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Role of Artichoke leaves Water Extract on Lipid Status on Rats Fed High Fat Diet

Abstract: High fat diet HFD induces excessive body fat content and lipid abnormalities. The importance of using medicinal plants becomes more patent in the present time Artichoke is a plant that traditionally used for treatment of different disease. The study aimed to investigate the role of supplementing low or high doses of water extract of artichoke leaves in rats fed HFD. For this purpose, four rat groups were established as follow: control group, high fat diet group, Low dose artichoke+ HFD group treated by low dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
1
1
0
Order By: Relevance
“…This finding was similar to the study carried out by Salem et al, (2017). Smilarly Abdulkhaleq et al, (2019) examined the effect of using low and high doses of water extract of artichoke leaves that given to 5255 rats observed a significant reduction in serum MDA level, and increased GSH level. Also Kaymaz et al (2017) reported that supplementation with aqueous extract of artichoke leaf of rat diet caused significant decrease of MDA level and significant increase of activity of SOD, GPx, and CAT in treatment group compared with control group.…”
Section: Blood Serum Constituentssupporting
confidence: 88%
See 1 more Smart Citation
“…This finding was similar to the study carried out by Salem et al, (2017). Smilarly Abdulkhaleq et al, (2019) examined the effect of using low and high doses of water extract of artichoke leaves that given to 5255 rats observed a significant reduction in serum MDA level, and increased GSH level. Also Kaymaz et al (2017) reported that supplementation with aqueous extract of artichoke leaf of rat diet caused significant decrease of MDA level and significant increase of activity of SOD, GPx, and CAT in treatment group compared with control group.…”
Section: Blood Serum Constituentssupporting
confidence: 88%
“…Consistent with our findings, Yıldız et al, (2008) reported that artichoke decreased serum triglyceride levels in laying hens. Smilarly, Abdulkhaleq et al, (2019) found that artichoke extract treatment decreased the triglyceride level when compared to HFD (high feed diet) group. Suarez et al, (2019) reported that high-fat diets supplemented with 20% of artichoke significantly reduced plasma triglyceride levels (34%), plasma LDL and VLDL (29%) and total (24%) cholesterol.…”
Section: Blood Serum Constituentsmentioning
confidence: 96%